2003
DOI: 10.1021/es034734y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Airborne Exposures of Teenagers to Manganese, Chromium, and Iron from Steel Dust and New York City's Subway System

Abstract: There is increasing interest in potential health effects of airborne exposures to hazardous air pollutants at relatively low levels. This study focuses on sources, levels, and exposure pathways of manganese, chromium, and iron among inner-city high school students in New York City (NYC) and the contribution of subways. Samples of fine particulate matter (PM2.5) were collected during winter and summer over 48 h periods in a variety of settings including inside homes, outdoors, and personal samples (i.e., sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
131
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(157 citation statements)
references
References 24 publications
20
131
1
2
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 PM collected at Beijing subway is found to have extremely high magnetic concentrations compared with the local street dust and surface soil samples (Table 3). This can be attributed to internal sources of iron-rich particles (Chillrud et al, 2004;Sitzmann et al, 1999). Suburban railway PM is also found to have high magnetic concentration; lower than particles from subway stations but much higher than naturally deposited particles.…”
Section: Magnetic Mineral Compositionmentioning
confidence: 94%
See 3 more Smart Citations
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 PM collected at Beijing subway is found to have extremely high magnetic concentrations compared with the local street dust and surface soil samples (Table 3). This can be attributed to internal sources of iron-rich particles (Chillrud et al, 2004;Sitzmann et al, 1999). Suburban railway PM is also found to have high magnetic concentration; lower than particles from subway stations but much higher than naturally deposited particles.…”
Section: Magnetic Mineral Compositionmentioning
confidence: 94%
“…As one of the most convenient public transportation systems for commuters, the Beijing subway has a passenger flow of ~10 million per day (www.bjsubway.com), the highest in the world. Due to the intrinsic nature of rail abrasion and train braking in the subway tunnels (Chillrud et al, 2004;Sitzmann et al, 1999), iron-containing particles can be generated and become suspended into the subway environment. Frictional abrasion contributes 40-73% of PM10s at the platforms in the Milan subway system in Italy (Colombi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crump reported that time spent in Toronto subways was the best predictor of manganese in personal blood samples in his study (Crump, 2000). Chillrud et al (2004Chillrud et al ( , 2005 studied personal exposures to iron, manganese, and chromium dust among students and workers in New York City (NYC) and found that the NYC subway is the dominant source of these exposures.…”
Section: Adverse Health Effectsmentioning
confidence: 99%